Core–shell hydrogel microcapsules enable formation of human pluripotent stem cell spheroids and their cultivation in a stirred bioreactor - Fattahi, Pouria (Sci Rep, 2021)
Cellular therapies based on human pluripotent stem cells (hPSCs) offer considerable promise for treating numerous diseases including diabetes and end stage liver failure. Stem cell spheroids may be cultured in stirred bioreactors to scale up cell production to cell numbers relevant for use in humans. Despite significant progress in bioreactor culture of stem cells, areas for improvement remain. In this study, we demonstrate that microfluidic encapsulation of hPSCs and formation of spheroids. A co-axial droplet microfluidic device was used to fabricate 400 μm diameter capsules with a poly(ethylene glycol) hydrogel shell and an aqueous core. Spheroid formation was demonstrated for three hPSC lines to highlight broad utility of this encapsulation technology. In-capsule differentiation of stem cell spheroids into pancreatic β-cells in suspension culture was also demonstrated.